HAS ANGER 1000 FACES? HOW CONSISTENT ARE THE FACIAL EMG PATTERNS OF DIFFERENT METHODS TO ELICIT FACIAL ANGER EXPRESSION OF VARYING INTENSITIES? - Rolko, Claudia; Eichstaedt, Jan; Dahme, Gisela; Dahme, Bernhard (Faculty of Psychology, Universitas Gadjah Mada, 2002)
Do the usual methods to elicit angry faces yield the same EMG patterns and are the EMG activations of weakly angry faces weaker than those of intensely angry ones? 23 males were asked (1) to imagine 6 vignettes with family conflict situations (3 eliciting weak, 3 eliciting intense anger), (2) first to assess for 30 new conflict situations in the family, anger intensity and how each vignette fits their own family situation and then to imagine those 6 ones, that - for each participant - were extreme in anger intensity and convenient to imagine, (3) to remember and imagine 2 self-expierienced individual conflict situations with a parent (1 intensely angry, 1 weakly angry), (4) to make faces of slight vs. severe anger (same with disgust and joy), and finally (5) to imitate the facial expression of photos from respective series expressing high / low anger, disgust and joy. EMGs were recorded from corrugator supercilii, orbicularis oculi, levator labii and zygomaticus major. The data show that different methods to induce angry faces of high vs. low intensity yield EMG patterns not consistent across methods. Methods (1) and (3) did not yield a significant intensity effect in corrugator activity, but methods (2), (4) and (5) did. There is a considerable method heterogenity of anger expression in orbicularis oculi, levator labii and zygomaticus (even between methods (4) and (5)). This is in contrast to the facial EMG effects of joy and disgust which are in the expected direction in both methods (4 & 5), The anger results are in accordance with Ekman who found that in anger expression more different Action Units are involved than in any other basic emotion. Keywords: EMG, Emotion, Anger, Facial Expression